Industrial legislation in Australia in 2018. (June 2019) - Rawling, Michael; Schofield-Georgeson, Eugene
It has been a quiet year like last year for the passing of federal industrial legislation (due to a number of factors, including the political turmoil of the federal coalition government and their lack of an overall labour law reform agenda). This article examines key federal industrial legislative developments including the Modern Slavery Act 2018 (Cth). The article identifies that the federal Act contains much weaker compliance measures than the counterpart New South Wales legislation also passed in 2018 – the Modern Slavery Act 2018 (NSW). Also, although the Coalition government has attempted to continue to prosecute its case for further union governance measures, this agenda has been less successful than in previous years, with key government Bills not yet passed by the Parliament. The stagnation in the federal Parliament continues to motivate certain State Parliaments to address worker exploitation, and the article goes on to examine key State industrial legislation passed in 2018 including the Victorian labour hire licensing statute. In light of the continuing dominant position of the federal Labor opposition in opinion polls and an impending federal election in 2019, the article concludes by briefly considering the federal Labor opposition's agenda for industrial legislation.